Extracts ofHylotelephiumerythrostictum (miq.) H. Ohba ameliorate intestinal injury by scavenging ROS and inhibiting multiple signaling pathways in Drosophila - Hyonil Kim; Xinyu Yi; Hongmei Xue; Guanhua Yue; Jiahua Zhu; Tongju Eh; Sihong Wang; Li Hua Jin (BMC, 2024)
Abstract Background The intestinal epithelial barrier is the first line of defense against pathogens and noxious substances entering the body from the outside world. Through proliferation and differentiation, intestinal stem cells play vital roles in tissue regeneration, repair, and the maintenance of intestinal homeostasis. Inflammatory bowel disease (IBD) is caused by the disruption of intestinal homeostasis through the invasion of toxic compounds and pathogenic microorganisms. Hylotelephium erythrostictum (Miq.) H. Ohba (H. erythrostictum) is a plant with diverse pharmacological properties, including antioxidant, anti-inflammatory, antidiabetic, and antirheumatic properties. However, the roles of H. erythrostictum and its bioactive compounds in the treatment of intestinal injury are unknown. Methods We examined the protective effects of H. erythrostictum water extract (HEWE) and H. erythrostictum butanol extract (HEBE) on Drosophila intestinal injury caused by dextran sodium sulfate (DSS) or Erwinia carotovoracarotovora 15 (Ecc15). Results Our findings demonstrated that both HEWE and HEBE significantly prolonged the lifespan of flies fed toxic compounds, reduced cell mortality, and maintained intestinal integrity and gut acid‒base homeostasis. Furthermore, both HEWE and HEBE eliminated DSS-induced ROS accumulation, alleviated the increases in antimicrobial peptides(AMPs) and intestinal lipid droplets caused by Ecc15 infection, and prevented excessive ISC proliferation and differentiation by inhibiting the JNK, EGFR, and JAK/STAT pathways. In addition, they reversed the significant changes in the proportions of the gut microbiota induced by DSS. The bioactive compounds contained in H. erythrostictum extracts have sufficient potential for use as natural therapeutic agents for the treatment of IBD in humans. Conclusion Our results suggest that HEWE and HEBE are highly effective in reducing intestinal inflammation and thus have the potential to be viable therapeutic agents for the treatment of gut inflammation. Clinical trial number Not applicable.